Avaliação cromatográfica e atividade Antimicrobiana de produtos preparados com NIM (Azadirachta indica A. Juss., Meliaceae): Azadirachta indica A. Juss.; Meliaceae) - Priscila Drumond Alves (2007)
Neem (Azadirachta indica A. Juss., Meliaceae) is an Indian tree well known for its pesticide activity and several pharmacological activities, including a wide spectrum activity against pathogenic microorganisms. More than 300 compounds have already been isolated and azadirachtin (AZA) is its main active component. In the present work, Neem leaves hydroalcoholic extracts were prepared by percolation in differentethanol concentrations (50%, 60%, 70%, 80% e 90% (V/V)). The presence of AZA was verified by thin-layer chromatography (TLC) and by high performance liquid chromatography (HPLC-UV/DAD) using isocratic and gradient modes. Both for the extracts and the commercial Neem products, the AZA presence was determined by TLC and HPLC, as described above, and tested against Gram-positive and Gramnegativebacteria, fungi and yeasts. Analytical curves were carried out by injectingincreasing volumes (10 to 30 ml) from AZA stock standard solution (0.4 mg/ml). The isocratic method presented better linearity (r = 0.9985) and shorter retention times for the two evaluated peaks (average Rt = 7.933 min and 8.780 min) than the gradient method (average Rt = 17.305 min e 18.872 min), hence was recommended for AZA estimate quantitation. The extracts did not display equivalent AZA spot by TLC. Out of six commercial products analyzed, all presented a great variety in AZAamount and only two showed the AZA correspondent peaks. The extracts prepared with 70% and 80% (V/V) ethanol showed activity against Staphylococcus aureus, however, no dose-dependent activity was detected, according to Tukeys test (q0.05;3;7). Only one of the six products tested showd antimicrobial activity. The absence of AZA in those extracts or products indicates that the activity may be due to the presence of other substances.